The Effect of the Discussing-Practicing-Reflection Technique on Basic Teaching Skills and Developing PAI Learning Tools in Scientific Approach - Nuraini Nuraini; Hamzah Hamzah (Universitas Negeri Makassar, 2021)
This study aims to see and describe how the process of implementing lectures using the Discussion-Practice-Reflection technique improves the ability to improve basic teaching skills and the ability to develop learning tools with a scientific approach. The research approach used is quantitative and quasi-experimental methods with a research sample of 24 students (5th semester PAI course participants) by total sampling technic. Based on the data and descriptions of the division that has been carried out, it can be concluded that the DPR learning technique has a positive effect on the two variables tested, namely: basic teaching skills and the ability to develop learning tools in scientific approach. It can be seen from the results of the test that 50% of the students got “very good”, then 37.5% got “good” and 12.5% got “enough”. It can also be said that the use of DPR techniques in developing basic teaching skills was quite successful. Regarding the ability to develop learning tools, as many as 37.5% of students got “very good”, then 46% got “good” and 16.5% got a “enough”. It can also be said that the use of DPR techniques in developing learning tools skill with a scientific approach is quite successful.